Vertical flow immunoassay for multiplex mycotoxins based on photonic nitrocellulose and SERS nanotags - Ruipeng Chen; Jingfang Hu; Hui Wang; Cheng Li; Haiqi Kang; Yuxuan Chen; Liang Yang; Xiangfang Tang; Benhai Xiong; Xiangwei Zhao (Food Chemistry: X)
Here, we report a SERS based VFA using PNC as a sensing substrate for highly sensitive multiplex mycotoxins detection. The PNC was fabricated by filtration-based self-assembled monodisperse SiO2 NPs on a filter membrane as a template, and the obtained PNC had an ordered complementary inverse opal structure. In parallel, three kinds of Raman dyes encoding Au@NBAAg, Au@4-MBAAg and Au@DNTBAg SERS nanotags were synthesized for the detection of OTA, AFB1 and ZON. In the immunoassay, because of the slow-photon effect of the PNC substrate, which facilitates the light coupling with SERS nanotags, the SERS signal was highly enhanced. The LODs of 8.2, 13.7 and 47.6 fg mL−1 were achieved for simultaneous detection of OTA, AFB1 and ZON, respectively, which were lower than the tolerable cutoff values recommended by the EC. Therefore, this proposed PNC based SERS VFA is expected to be a powerful method for multiplex mycotoxins detection.